Analysis of Digital Transformation in Logistics and Supply Chain Management in India and Nepal an Innovation at Madhesh University - Mishra, Anjay Kumar (Madhesh Journal of Interdisciplinary Research, 2026)
This editorial illustrates the impactful research and innovation at Madhesh University through collaboration grounded in a published Indian patent (application no. 202641017633) on “Analysis of Digital Transformation in Supply Chain Logistics Management,” verified in 2026 at iprsearch.ipindia.gov.in. These engagements signify more than institutional partnerships; they represent Madhesh University’s integration into the global academic community. Through conferences, collaborative research, and scholarly exchanges, the university builds networks that facilitate innovation, strengthen research capacity, and promote international visibility. Here, we share Madhesh University’s achievements on “Analysis of Digital Transformation in Logistics and Supply Chain Management” in India and Nepal. This patent is named under Dr. Anjay Kumar Mishra, Dr. Tara Prasad Gautam, Dr. Shila Mishra, Dr. Binod Lingden, and Prof. Dr. Mahananda Chalise, highlighting their collaborative contribution to advancing digital transformation in supply chain logistics across both nations. In general, digital transformation is a factor that contributes to the modernization of supply chains in a sustainable manner and to economic progress in both countries.